(3GdCSQG Edi GdebGe GdCSQGs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3CMeO Hf eMeO Hf WGQGeGe s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd eMji GdOjf CHh YHO Gddg eMeO Hf Ydi GHf GdYQHi CeG HYO aEfi bUOJ eYGTQ GdUhajI ai gPG GdcJGH GdESQG Edi GdebGe GdCSQG hGNJUGQ JQJjH GdQMdg s
(3BNQgG (B:s
(3bGd GdeDda QMeg Gddg JYGdi LejY eG ai gPG GdESQGQ ef GdfXe di Shi CQHYI CHjGJ hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg JeJ GdQSGdI GdeHGQcI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B114s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B82s
Keywords: (3GdJUha hGdBOGH GdTQYjIs